2014
DOI: 10.1002/2013jb010290
|View full text |Cite
|
Sign up to set email alerts
|

PandSwave velocity measurements of water-rich sediments from the Nankai Trough, Japan

Abstract: Acoustic velocities were measured during triaxial deformation tests of silty clay and clayey silt core samples from the Nankai subduction zone (Integrated Ocean Drilling Program Expeditions 315, 316, and 333). We provide a new data set, continuously measured during pressure increase and subsequent axial deformation. A new data processing method was developed using seismic time series analysis. Compressional wave velocities (V p ) range between about 1450 and 2200 m/s, and shear wave velocities (V s ) range bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 75 publications
7
12
0
Order By: Relevance
“…The laboratory velocities are consistent with seismicreflection models that indicate the velocity should range between 1.5-3.0 km/s in the frontal prism sediments in the Japan Trench (Murauchi and Ludwig, 1980;Miura et al, 2001Miura et al, , 2005Nakamura et al, 2014). They also agree with ultrasonic wave-speed measurements of prism sediments from other subduction zones (Carson and Bruns, 1980;Tobin et al, 1994Tobin et al, , 1995Tobin and Moore, 1997;Gettemy and Tobin, 2003;Hashimoto et al, 2010;Raimbourg et al, 2011;Schumann et al, 2014). For the purposes of this study, we are mainly interested in the average elastic properties of the prism.…”
Section: P-and S-wave Speedssupporting
confidence: 78%
See 3 more Smart Citations
“…The laboratory velocities are consistent with seismicreflection models that indicate the velocity should range between 1.5-3.0 km/s in the frontal prism sediments in the Japan Trench (Murauchi and Ludwig, 1980;Miura et al, 2001Miura et al, , 2005Nakamura et al, 2014). They also agree with ultrasonic wave-speed measurements of prism sediments from other subduction zones (Carson and Bruns, 1980;Tobin et al, 1994Tobin et al, , 1995Tobin and Moore, 1997;Gettemy and Tobin, 2003;Hashimoto et al, 2010;Raimbourg et al, 2011;Schumann et al, 2014). For the purposes of this study, we are mainly interested in the average elastic properties of the prism.…”
Section: P-and S-wave Speedssupporting
confidence: 78%
“…At other subduction zones, it has been suggested that the occurrence of shallow coseismic slip is due to the presence of unusually competent and strong sediments which allow the accumulation and release of elastic energy (Gulick et al, 2011). To test this hypothesis, we examined ultrasonic velocity measurements that have been collected on shallow accretionary prism sediments retrieved from other subduction zone margins by IODP, DSDP, and Ocean Drilling Program (ODP) projects (Tobin et al, 1994(Tobin et al, , 1995Tobin and Moore, 1997;Gettemy and Tobin, 2003;Hashimoto et al, 2010;Raimbourg et al, 2011;Schumann et al, 2014). We compared our computed elastic properties to published data from other accretionary prisms to address whether a difference in the elastic properties could account for the occurrence of coseismic slip to the trench during the Tohoku earthquake.…”
Section: Comparison Of Global Subduction Zone Elastic Modulimentioning
confidence: 99%
See 2 more Smart Citations
“…During compaction, platy grains typically rotate from a less ordered orientation with predominantly edge‐to‐edge and edge‐to‐face contacts towards an alignment parallel to the seafloor with predominantly face‐to‐face contacts resulting in crystallographic preferred orientations (textures; Bennett et al, ; Bennett & Hulbert, ; Milliken & Reed, ). As for platy phyllosilicates crystallographic and shape preferred orientations are closely linked, textures can control the physical properties and deformation behavior of such sediments (e.g., Carson et al, ; Hashimoto et al, ; Kock & Huhn, ; Mondol et al, ; Oertel, ; Schumann, Stipp, Behrmann, et al, ), hence the strain distribution in active continental margins and also the frictional behavior in the forearc wedge as well as in the subduction channel along the plate boundary interface. Sediment strength, friction, and related seismogenic behavior are governed by, among other parameters, the mineralogical composition and fabric and their relevant physical properties (e.g., Kopf, ; Stipp et al, ; Schumann, Stipp, Leiss, et al, ).…”
Section: Introductionmentioning
confidence: 99%